(untitled) (Applied Biological Research, 2012)
Peste des petits ruminants (PPR) is a highly infectious and contagious disease of sheep and goats characterized by stomatitis, diarrhoea, occulonasal discharge and pneumonia. PPR virus enters the host through respiratory tract, and its major site for replication is lymphoid tissues (Tatsuo et al., 2001). After entering upper respiratory tract, the virus exhibits pronounced tropism for monocytic and lymphocytic cells and soon replication is detected in draining lymph nodes. Following replication in lymphoid tissues, virus spreads to various organs. Recently, it has been reported that signaling lymphocytic activation molecule (SLAM) or CD150, a membrane glycoprotein, acts as receptor for measles virus, canine distemper virus and rinderpest virus (Seki et al., 2003 and Techangamsuwan et al., 2010) prompted us to hypothesize that the same molecule may contribute for infection in PPR also. Keeping in view the above facts, the present investigation was aimed to study the tissue tropism of PPR virus.